Analisis Indeks Pembangunan Manusia Di Provinsi Jambi: Analisis Indeks Pembangunan Manusia Di Provinsi Jambi - Lesly, Lesly Ghina Devina; Tan, Syamsurijal; Umiyati, Etik; Khodijah, Siti; Nurhayani, Nurhayani (Jurnal Khazanah Intelektual, 2026)
This study aims to analyze the influence of expenditure index, population density, poverty, unemployment, and investment on the human development index in regencies and cities in Jambi Province for the period 2018–2024. The research method used quantitative descriptive analysis. The research objects are regencies and cities in Jambi Province during the period 2018-2024. The analytical tool used is Panel Data regression. The results of the study indicate that expenditure index, population density, and poverty rate affect the human development index in regencies and cities in Jambi Province from 2018 to 2024, while unemployment rate and investment do not affect the human development index in regencies and cities in Jambi Province during the same period